EXTRACURRICULAR WORK AS AN EDUCATIONAL MEANS PROFESSIONAL EDUCATION - Kuzmenko, N.V. (Pedagogy of Higher and Secondary Education, 2008)
The attempt to define components of system of extracurricular pedagogical work as an educational mean of professional education is made in this article.